Inverse Association of Plasma Level of Glutathione Peroxidase with Liver Fibrosis in Chronic Hepatitis B: Potential Role of Iron - Moossavi, Shirin (Middle East J Dig Dis, 2016)
BACKGROUND Oxidative stress has a major pathogenic role for liver damage following chronic hepatitis B. Glutathione peroxidase (Gpx) is necessary in oxidative state mechanism that is generally down-regulated by Hepatitis B virus (HBV) infection. On the other hand, disorders of iron homeostasis have been found out in HBV infected patients. Therefore, the objective of this study was to assess the interplay of Gpx and serum iron on clinical and virological features of patients with chronic HBV infection. METHODS One hundred and fifty adult, treatment-naïve, patients with chronic hepatitis B were randomly designated from an ongoing cohort of patients with HBV. Plasma Gpx1 concentration and HBV DNA quantity were measured. Liver stiffness was measured by transient elastography. RESULTS Serum iron had a positive association with HBV DNA count in the total population. Serum iron was not associated with liver stiffness. However, HBV DNA was significantly associated with liver stiffness only in male patients. Serum Gpx was inversely associated with liver stiffness. Serum iron and Gpx had indirect effects on liver stiffness via HBV DNA count. We observed dissimilar effects of serum iron on HBV DNA and Gpx on liver stiffness in male and female patients. CONCLUSION We identified interplay of serum iron and Gpx1 in relation to level of liver fibrosis in patients with chronic hepatitis B. Our results propose that oxidative stress and serum iron are differentially implicated in the progression of chronic hepatitis B in male and female patients.